pegIT - a web-based design tool for prime editing - Anderson, Mads Valdemar; Haldrup, Jakob; Thomsen, Emil Aagaard; Wolff, Jonas Holst; Mikkelsen, Jacob Giehm (Nucleic acids research, 2021)
Abstract Prime editing (PE) is a novel CRISPR-derived genome editing technique facilitating precision editing without double-stranded DNA breaks. PE, mediated by a Cas9-reverse transcriptase fusion protein, is based on dual-functioning prime editing guide RNAs (pegRNAs), serving both as guide molecules and as templates carrying the desired edits. Due to such diverse functions, manual pegRNA design is a subject to error and not suited for large-scale setups. Here, we present pegIT, a user-friendly web tool for rapid pegRNA design for numerous user-defined edits, including large-scale setups. pegIT is freely available at https://pegit.giehmlab.dk. Graphical Abstract Graphical abstract pegIT is a freely available, user-friendly web tool that allows for easy and efficient pegRNA design for numerous, including large-scale, user-defined edits.